MODEL PEMBELAJARAN COOPERATIVE INTEGRATED READING AND COMPOSITION (CIRC) UNTUK MENINGKATKAN PRESTASI BELAJAR - Arthini, Ni Wayan Sari (Jurnal Santiaji Pendidikan (JSP), 2018)
Implementation of this study aims to determine the improvement of learning achievement of Indonesian students class III Semester II SD No. 3 Abiansemal 2015/2016 Academic Year after applying the Cooperative Integrated Reading And Composition (CIRC) learning model in the learning process. The initial problem that occurs is that the learning process has not been maximized by the teacher in improving student achievement due to the use of the Cooperative Integrated Reading And Composition (CIRC) learning model that still uses a model that is constantly being asked without adequate theory. After the data was collected using tools in the form of student achievement tests from an initial average of 67.38 with learning completeness of 26.92%, increased to 71.81 with learning completeness 57.69% in cycle I and rose to 78.54 with learning completeness 96.15% in cycle II. The results in the second cycle are in line with the expectations of the research success indicators therefore this study is not continued to the next cycle. With the acquisition of these data it can be ascertained that the application of the Cooperative Integrated Reading And Composition (CIRC) learning model method in the implementation of the learning process is able to improve the achievement of students' Indonesian learning so that the proposed hypothesis can be accepted.